Aesthetic functionalism as a principle of literary translation - О. В. Ребрій (Записки з романо-германської філології, 2015)
The article deals with the specifics of aesthetic function manifestations in literary translation as seen in linguistic and cultural paradigms of translation studies. Creative nature of translation was exposed as that of securing the unity of aesthetic ideals of the author, translator and recipient between source and target cultures, on the synchronic level of a target culture and the diachronic level of a target culture.